2000
DOI: 10.1046/j.1439-037x.2000.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Use Efficiency as a Factor Determining the Structure of Herbaceous Plant Communities in Low‐Nutrient Environments

Abstract: We tested the hypothesis that, in competition for nutrients, the plant species using more efficiently the limiting nutrient will tend to dominate in plant communities. Two experiments were conducted. In the first, plant communities consisting of perennial herbaceous species were grown in large boxes filled with soil enriched with all necessary nutrients, except for nitrogen (N) in half of the boxes and phosphorus (P) in the other half. It was expected that N or P, respectively, would become progressively limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…This contradicts statements proposing that, in nutrient competition, the most competitive species for a particular limiting nutrient are those that lower mostly the concentration of this nutrient in the soil solution (Tilman, 1982); these species tend to have the lowest tissue concentrations of this limiting nutrient (Tilman, 1990) and use more efficiently this nutrient. Confirming these statements, which are included in the of 'resource ratio model' of Tilman (1997), Mamolos et al (1995b) and Koutroubas et al (2000) found that species with lower concentrations of the limiting nutrients tended to dominate in plant communities. By working in the two sites of our study, Vasilikos (2001) also found similar results but only for the dry site.…”
Section: Responses Of Species To N and P Additionsmentioning
confidence: 73%
See 1 more Smart Citation
“…This contradicts statements proposing that, in nutrient competition, the most competitive species for a particular limiting nutrient are those that lower mostly the concentration of this nutrient in the soil solution (Tilman, 1982); these species tend to have the lowest tissue concentrations of this limiting nutrient (Tilman, 1990) and use more efficiently this nutrient. Confirming these statements, which are included in the of 'resource ratio model' of Tilman (1997), Mamolos et al (1995b) and Koutroubas et al (2000) found that species with lower concentrations of the limiting nutrients tended to dominate in plant communities. By working in the two sites of our study, Vasilikos (2001) also found similar results but only for the dry site.…”
Section: Responses Of Species To N and P Additionsmentioning
confidence: 73%
“…On the other hand, forbs were restricted by grasses in the less fertile dry site. Koutroubas et al (2000) provided evidence of increasing competitive ability of forbs against grasses with increasing P availability and Mamolos and Veresoglou (2000) reported dramatic changes in species composition after P enrichment, which favored the species with the highest P tissue concentration.…”
Section: Productivity and Species Composition Of Sitesmentioning
confidence: 98%
“…King & Buckney (2000) similarly found that although native species were present at sites supplied with urban stormwater run-off, an altered plant community was present, likely because the higher nutrient levels selected for the native species tolerant of these altered conditions. Koutroubas et al (2000) reported similar findings from their study of several herbaceous perennial species in a greenhouse study; species that could more efficiently use a limiting nutrient had a competitive advantage over those species with lower nutrient use efficiency within a lownutrient habitat or plant community. However, changing water levels are part of the normal hydrology of stream communities (King & Buckney 2000), so some changes in native plant composition are to be expected and would not necessarily be attributable to changes in nutrient levels.…”
Section: R Simplexmentioning
confidence: 52%
“…The high soil nutrient levels may have selected for a certain palate of tolerant species, such as the primarily early succession native annuals and perennials as well as novel invaders (Appendices S1 and S2) that were present. Efficiency of nutrient use, a trait linked to invasibility of some species, and high soil nutrient levels may explain why so many of the species represented in the higher species richness of the seed bank were not present in the vegetation cover (King & Buckney 2000;Koutroubas et al 2000). Anaerobic soil conditions, like those found in floodplain forest soils, can absorb more P from high-P solutions (Patrick & Khalid 1974), like soil water that has increased levels resulting from urban run-off.…”
Section: R Simplexmentioning
confidence: 99%
“…Marriott et al 2002). Species adapted to low soil nutrient availability will increase in their abundance and can replace the nutrient-demanding species (Aerts 1999;Koutroubas et al 2000). In our case, the decrease in management intensity must have caused a transient phase of vegetation development.…”
Section: Factors Influencing the Occurrence Of Senecio Aquaticusmentioning
confidence: 81%